Pacification in Algeria, 1956-1958 - Galula, David (RAND Corporation, 2023)
When Algerian nationalists launched a rebellion against French rule in November 1954, France was forced to cope with a varied and adaptable Algerian strategy. In this volume, originally published in 1963, David Galula reconstructs the story of his highly successful command at the height of the rebellion. This groundbreaking work, with a new foreword by Bruce Hoffman, remains relevant to present-day counterinsurgency operations.